Pharmacognostic and phytochemical investigation of young leaves of Triticum aestivum Linn. - Jain, Gaurav; Argal, Ameeta (International Current Pharmaceutical Journal, 2014)
ABSTRACT The aim of the work is to perform the pharmacognostic study of the leaves of plant Triticum aestivum Linn., Family Poaceae, commonly known as Wheatgrass. It is cultivated on large scale all over India and also occasionally cultivated in garden. For the present study samples of the Wheatgrass leaves were collected over a specific period of nine days. The drug was cultivated with specific type of hybrid seeds obtained from most reputed institution of India and were scrupulously analysed. For standardization of the herbal drug morphological, phytochemical, physicochemical and microscopical examination was done. The leaves grown were found to be lax, cauline, flat, 0.6 to 0.25 inches (4 to 6 mm) wide, 6-9 inches long and green in color. The chemical compositions of the leaves are proteins, flavonoids, alkaloids, glycosides, terpenoides, saponins, fibers, tannins and phenolic compounds. The specific variety of seeds, specific time of collection made it more specific to be used for further pharmacological studies. DOI: http://dx.doi.org/10.3329/icpj.v3i6.18760 International Current Pharmaceutical Journal, May 2014, 3(6): 280-285